Implementation of Temperature and Humidity Control in Tiramite Mushroom Cultivation Based on IoT - Saprudin, Raihan Muhammad; Ibrahim, Rohmat Nur; Risanti, Rini; Suherman, Asep (LPPM STMIK Mardira Indonesia, 2025)
The development of tiramite mushrooms in Indonesia encounters difficulties in sustaining ideal temperature and humidity levels, particularly due to erratic climate variations. This study utilizes Internet of Things (IoT) technology to resolve these challenges by creating an automated, real-time system for monitoring and controlling temperature and humidity at JJ Srister Mushroom. The Research & Development (R&D) methodology employing a prototyping approach facilitates ongoing testing and enhancement of the system. This system employs DHT22 sensors and interfaces with a web page and control box for real-time monitoring. Test results indicate that the system effectively regulates temperature and humidity within suitable parameters for the growth phases of mycelium and mushroom fruit bodies, maintaining temperatures of 22-28°C and humidity levels of 80-90% during the mycelium phase, and temperatures of 16-25°C with humidity levels of 90-95% during the fruit body phase. The authors assert that this IoT system offers significant advantages and advocate for further investigation to enhance sensor precision and develop a mobile application as a supplementary monitoring tool.